Negative correlation of serum total bile acid with albuminuria in patients with Type 2 Diabetes Mellitus: A cross-sectional study. - Dash, Pratap Kumar; Panda, Madhusmita; Sahoo, Duryodhan (Student's Journal of Health Research Africa, 2025)
Background Type 2 diabetes mellitus (T2DM) is a leading cause of diabetic nephropathy, in which albuminuria serves as a key marker of renal damage. Bile acids are increasingly recognized as metabolic signaling molecules with potential roles in glucose and lipid regulation. This study examined the association between serum total bile acid (TBA) levels and albuminuria in patients with T2DM. Methods A single-center, cross-sectional study was conducted from January 2023 to December 2023 at Dharanidhar Medical College and Hospital (DDMCH), Keonjhar. One hundred adults with confirmed T2DM were enrolled. Clinical and biochemical data, including fasting serum total bile acid levels and first-morning urine albumin-to-creatinine ratio (UACR), were collected. Pearson’s correlation coefficient assessed the relationship between TBA and log-transformed UACR, and multivariable linear regression was performed to control for confounders such as age, HbA1c, and duration of diabetes. Results The cohort comprised 55 men and 45 women (mean age 58.5 years). A significant negative correlation was observed between serum TBA and log-transformed UACR (r = −0.55, p < 0.001). Mean serum TBA levels progressively decreased with increasing albuminuria: 5.7±1.5 µmol/L in normoalbuminuria, 3.9±1.2 µmol/L in microalbuminuria, and 2.4±0.8 µmol/L in macroalbuminuria. This association remained significant after adjusting for confounding variables (p < 0.01). Conclusion Serum total bile acid may represent a novel and easily accessible biomarker for assessing renal health and risk stratification in patients with T2DM. The results point to bile acids' possible protective function in the development of diabetic nephropathy. Recommendations This study provides a strong rationale for further large-scale, prospective research to confirm this relationship and explore the therapeutic potential of bile acid modulation.